Prevalence of Malnutrition among Patients with Type-2 Diabetes Mellitus in Tertiary Care Hospital in Pakistan - Ahmad, Ibrar; Kaifi, Hoor Maab; Ullah, Fahim; Javed, Adan; Tahir, Hira; Rahman, Mujeeb Ur (American Journal of Health, Medicine and Nursing Practice, 2022)
Purpose: To figure out the prevalence of malnutrition among patients with Type-2 Diabetes Mellitus (T2DM) in tertiary care hospital Methodology: The study adopted a cross-sectional study. The study took place in Endocrine and Medicine Departments of Lady Reading Hospital, Peshawar, Pakistan from September 2019 to March 2020. A total number of 259 patients of T2DM were screened for screened for nutritional assessment with the help of nurse and supporting staff. The data was recorded with the help of question are and Subjective Global Assessment form (SGA). The nutritional risk parameters and malnutrition status was figured out and the data collected was statistically analyzed with the help of MS Excel and SPSS 22.0. Findings: The results of the current findings revealed that 123 patients out of 259 were at moderate risk of malnutrition, while 136 patients were highly at malnutrition risk. Similarly, 162 patients were sorted out to have the status of moderate malnutrition while 97 patients were severely mal-nourished. Among various categories of BMI the highest frequency has been shown by Obese Class-I with highest risk malnutrition risk and severe malnourished frequency. The Correlation Coefficient R2 value of 0.923. The Chi-Square value of 187.69 and p-value (1.214e-38) nullifies the Null hypothesis. Conclusion: Based on the findings of this study, it may be concluded that a wholesome ratio of T2DM are at nutritional risk or having the status of malnutrition in hospitalized patients. Secondly, it may also be inferred that the largest number of T2DM could be assumed at Obese Class-I of BMI distribution.